Comparative Analysis of In Vivo and In Vitro Virulence Among Foodborne and Clinical Listeria monocytogenes Strains - Hui Yan; Biyao Xu; Binru Gao; Yunyan Xu; Xuejuan Xia; Yue Ma; Xiaojie Qin; Qingli Dong; Takashi Hirata; Zhuosi Li (Microorganisms)
Listeria monocytogenes is one of the most important foodborne pathogens that can cause invasive listeriosis. In this study, the virulence levels of 26 strains of L. monocytogenes isolated from food and clinical samples in Shanghai, China, between 2020 and 2022 were analyzed. There were significant differences among isolates in terms of their mortality rate in Galleria mellonella, cytotoxicity to JEG-3 cells, hemolytic activity, and expression of important virulence genes. Compared with other STs, both the ST121 (food source) and ST1930 (clinic source) strains exhibited higher G. mellonella mortality. The 48 h mortality in G. mellonella of lineage II strains was significantly higher than that in lineage I. Compared with other STs, ST1930, ST3, ST5, and ST1032 exhibited higher cytotoxicity to JEG-3 cells. Based on the classification of sources (food and clinical strains) and serogroups (II a, II b, and II c), there were no significant differences observed in terms of G. mellonella mortality, cytotoxicity, and hemolytic activity. In addition, ST121 exhibited significantly higher hly, inlA, inlB, prfA, plcA, and plcB gene expression compared with other STs. A gray relation analysis showed a high correlation between the toxicity of G. mellonella and the expression of the hly and inlB genes; in addition, L. monocytogenes may have a consistent virulence mechanism involving hemolysis activity and cytotoxicity. Through the integration of in vivo and in vitro infection models with information on the expression of virulence factor genes, the differences in virulence between strains or subtypes can be better understood.